Patients’ Perceptions of Health Care Providers’ Communication in Nigerian Hospitals - Aliyu, Muhammad Mukhtar; Kura, Aminu Umar; Gamawa, Alhaji Usman (Ikatan Sarjana Komunikasi Indonesia, 2024)
This study investigates patients' perceptions of healthcare providers' communication in Nigerian hospitals. The study adopts a survey research design and 177 patients were randomly selected from six hospitals in Northeastern Nigeria. Data were collected through a questionnaire. The data were subjected to descriptive statistical analysis and independent sample t-tests. The results of the analysis indicate that most of the patients have moderate perceptions towards the health care providers’ communication in hospitals in Nigeria, in terms of communication clarity, respect, and information adequacy. The study results highlight notable variations in patient perceptions of communication, revealing significant differences influenced by various sociodemographic factors. Notably, patients residing in rural areas have more positive perceptions than those residing in urban areas. Also, those aged 45 years and above exhibited higher rates of positive perceptions than those of 18 to 44 years old. Similarly, patients in private hospitals have higher positive perceptions compared to those attending public hospitals. Finally, patients with no formal education have higher levels of positive perceptions than those with formal education. The study makes recommendations for enhancing communication practices in Nigerian hospitals and suggestions for future research.